Mission Planner: An Open-Source Alternative to Commercial Flight Planning Software for Unmanned Aerial Systems - Jesse Chintanadilok; Sahaj Patel; Yilin Zhuang; Aditya Singh (EDIS)
All UASs need periodic maintenance and repair. These changes have raised questions among Extension agents regarding which UASs to purchase and use, and how these changes affect their operations going forward. Free and open-source (FOSS) options may be a very useful alternative to commercial-off-the-shelf (COTS) UASs. Written by Jesse Chintanadilok, Sahaj Patel, Yilin Zhuang, and Aditya Singh, and published by the UF/IFAS Department of Agricultural and Biological Engineering, August 2022.